More Hip Hop, Please! Exploring the Intersections of Public Theology and Hip Hop Studies - Tretter, Max (International journal of public theology, 2025)
So far, there are only a few points of contact between public theology and Hip Hop, let alone a systematic exploration of Hip Hop’s potential contributions to public theology or insights into mutual learnings between Hip Hop Studies and public theology. This article addresses this gap by conceptually identifying common ground between Hip Hop Studies and public theology. Building on this foundation, it posits that public theology could learn from Hip Hop Studies (1) to include Hip Hop as an important witness to the lived reality of marginalized individuals in their own reflections; (2) to have more courage for positionality, (3) and to give greater consideration to aesthetic formats in their own reflections. Conversely, Hip Hop Studies can learn from public theology (1) to consider the aspect of Hip Hop’s publicity from the outset in their analysis and (2) to adopt a critical perspective towards problematic elements in Hip Ho